Genetic associations of plasma amino acid levels with male hypogonadism, erectile dysfunction and infertility - Xing Hu; Congcong Zou; Tianhong Wang; Leng Zhou (Journal of Men's Health, 2024)
Amino acids are involved in male reproductive health. However, a comprehensive survey exploring the role of amino acids in male hypogonadism, erectile dysfunction and male infertility is still lacking. To address this concern, summary-level statistics of 20 amino acids in plasma, testosterone, sex hormone binding globulin, bioavailable testosterone, erectile dysfunction and male infertility were obtained from previously published genome-wide association studies. The genetic correlation between amino acids and male reproductive health was determined by linkage disequilibrium score regression. An inverse variance weighting estimator was employed toprovide causal inference, supplemented by Mendelian Randomization (MR)-Egger, Weighted median, Maximum likelihood, MR. robust adjusted profile score and MR- Pleiotropy Residual Sum and Outlier estimators for sensitivity analyses. The unit of serum amino acids is 1-standard deviation of log-normalized values. The inverse variance weighting estimator found that as per unit increase in serum isoleucine, the concentration of bioavailable testosterone decreased by 0.013 standard deviations (95% confidence interval (CI) = 0.024–0.002, p = 0.021). There was a significant genetic correlation between serum lysine and erectile dysfunction (rg = −0.484, p = 0.025). A one-unit increase in serum lysine corresponded to a 0.93-fold risk of erectile dysfunction (95% CI = 0.88–0.99, p = 0.015). One unit increase in genetically predicted serum levels of isoleucine, leucine and tyrosine corresponded to a 1.08-fold (95% CI = 1.01–1.15, p = 0.030), 1.09-fold (95% CI = 1.02–1.17, p = 0.008), and 1.09-fold (95% CI = 1.01–1.18, p = 0.033) increased risk of male infertility, respectively. Sensitivity analyses confirmed these results. No pleiotropy and heterogeneity were identified. These findings highlight the risky role of plasma amino acids in the occurrence of male hypogonadism, erectile dysfunction and male infertility. Early identification and intervention for plasma amino acids overload or deficiency may be beneficial to male reproductive health.